2010
DOI: 10.1007/s10071-010-0319-8
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual and age differences in exploration, neophobia and problem-solving ability in a Neotropical raptor (Milvago chimango)

Abstract: Animal innovations have far-reaching ecological and evolutionary consequences. The occurrence and persistence of an innovation require several processes, including exploration, social and asocial learning, and low neophobia. In addition, the identity of the innovator may determine how these new behaviours are socially transmitted. Taking into account inter-individual and age differences, we investigated three correlates of animal innovation: object exploration, neophobia level and novel problem-solving ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
118
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 47 publications
7
118
2
Order By: Relevance
“…However, observations of high levels of neophobia are repeatable and can correlate across contexts (e.g. decreased use of structure and poorer problem solving [29,30]). Likewise, numerous studies have explored variation in predator neophobia across populations and species (e.g.…”
Section: Predator Neophobia Overviewmentioning
confidence: 99%
“…However, observations of high levels of neophobia are repeatable and can correlate across contexts (e.g. decreased use of structure and poorer problem solving [29,30]). Likewise, numerous studies have explored variation in predator neophobia across populations and species (e.g.…”
Section: Predator Neophobia Overviewmentioning
confidence: 99%
“…Furthermore, it has been shown that raptors differ in their head movements, which could reflect different foraging tactics (O'Rourke et al, 2010b). Because inter-individual problem-solving abilities have been found in a raptorial species, the chimango caracara, Phalcoboenus chimango (formerly named as Milvago chimango; Biondi et al, 2010), it is possible that individuals may also differ in their behaviour when presented with a visually challenging task; for instance, the number of head movements may differ before making a visual discrimination or there may be differences in the time delay before showing a response towards a stimulus. These behavioural differences may also reflect inter-individual differences in visual capacity, particularly of visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“…Exploration is typically quantified by examining the extent to which an individual investigates a novel area or object, including measures such as the time spent in the novel area, the amount of space the individual covers, the amount of time spent near the novel object, the number of sides or parts of the object contacted, or the latency to approach novel objects in their environment [8,13,14,[28][29][30][31][32]. In this study, we focused on the variety of behaviours that hyenas exhibited when interacting for the first time with a novel problem-solving apparatus, and thus we did not rely exclusively on these traditional temporal or spatial measures.…”
Section: Introductionmentioning
confidence: 99%